Biological and Methotrexate Survival after Pregnancy in Patients With a Rheumatic Disease - Tahmasian, Helena; Smeele, Hieronymus T. W.; de Jong, Pascal H.P.; Dolhain, Radboud J. E. M.; van Mulligen, Elise (Frontiers in Pharmacology, 2022)
Objective: Patients with a rheumatic disease who discontinue their disease-modifying anti-rheumatic drug (DMARD) due to pregnancy often wonder if treatment will be as effective after pregnancy. This study investigates the effect of a temporary discontinuation of DMARDs due to pregnancy on the effectiveness of the same DMARD postpartum in patients with a rheumatic disease. Methods: Pregnant, rheumatic patients were derived from the Preconceptional Counseling in Active Rheumatoid Arthritis (PreCARA) cohort. DMARD-survival after pregnancy, for biological and methotrexate (MTX) therapy, was analyzed and compared to controls with stable DMARD-treatment from a retrospective cohort. Results: In total, 234 patients were included, of whom 114 patients had stable biological or MTX treatment before their pregnancy. After pregnancy, 40 out of 56 (71%) patients restarted their biological, for MTX this was 49%. One year after restart, and censoring for a following pregnancy, 88.9% of patients were still using their biological, and 85% still used their MTX (p=0.92). Compared to the matched controls the survival after pregnancy was significantly lower one year after restart for both biologicals (98.3%) and MTX (99.6%); p=0.002 and p<0.001 respectively; three years after restart this significant difference was no longer observed (p=0.50 and p=0.33, respectively). Conclusion: Effective DMARD (biological or MTX) treatment before pregnancy that was discontinued due to pregnancy seems effective after pregnancy. Although DMARD-survival was higher in the control group one year after restart, the percentage of patients with effective treatment was still very good (>85%). In addition, this difference was no longer observed after three years.